Simulated impacts of anthropogenic land-cover change on the mesoscale climate of the Florida Peninsula - Marshall, Curtis Hal, author; Pielke, Roger A., Sr., advisor; Cotton, William R., committee member; Denning, A. Scott, committee member; Coughenour, Michael B., committee member; Steyaert, Louis T., committee member (Colorado State University. Libraries, 2004)
Datasets representing both natural and current land cover on the Florida peninsula were implemented in the Regional Atmospheric Modeling System to simulate the impacts of anthropogenic land-cover change on the mesoscale climate of the region. Implementation of current land cover in simulations of three recent July-August periods resulted in generally increased daily maximum temperature, especially along an interior north-to-south axis corresponding to natural wetlands within the Kissimmee River basin and south of Lake Okeechobee that were drained during the 20th Century. In the natural land-cover case, this axis was associated with a local minimum in sensible heat flux, which served to generate a horizontally divergent mesoscale wind that reinforced the convergence along the adjacent sea-breeze fronts. This feature was diminished or altogether absent in the simulations with current land cover, because those wetlands were largely drained during the 20th Century. As a result, the simulated convergence along the adjacent sea-breeze fronts was weakened, and the divergence along the interior axis was diminished. This mechanism resulted in decreased rainfall along the sea-breeze fronts and increases along the interior axis. When expressed as an average over the model domain, the convective rainfall was decreased 10-12% from the natural case total. These results provide evidence of a physical-dynamical mechanism that links the mesoscale spatial distributions of the changes in land cover, surface fluxes, the sea-breeze circulations, and convective rainfall with a regional-scale decrease in warm season rainfall. These results were consistent when subjected to a variety of model sensitivity tests. The differences in grid-average rainfall and daily maximum temperature are also consistent with long-term trends derived from an analysis of observational data. The two land-cover datasets were also applied to simulate three recent (and climatologically rare) damaging freeze events in south Florida. In most areas of the model domain where wetlands were drained and converted to agriculture during the 20th Century, minimum temperatures were colder when current land cover was implemented. Further examination of one event reveals that if wetlands were specified, the resulting increased heat capacity of the surface and a persistent water vapor flux acted to diminish the cooling rate of the lower atmosphere, thereby altogether preventing the development of freezing conditions at a location where crop losses totaled US $300M. With current land cover (agriculture), subfreezing temperatures developed and persisted for five hours. The results presented in this work suggest that anthropogenic land-cover changes have significantly impacted several aspects of the mesoscale climate of the Florida Peninsula. The results of this study also support previous studies in concluding that perturbations introduced to the climate system through anthropogenic land-cover change are physically and socioeconomically significant.
Keywords: atmosphere; geophysics; environmental science